GREEN ENTREPRENEURSHIP IN INCREASING INCOME OF FAMILY BUSINESS AT KERANGGAN ECOTOURISM - Kusumaningsih, Ani (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This conceptual paper discusses about green entrepreneurship which will be developed at Keranggan ecotourism in South Tangerang, which has an impact to increase their income for family business. The example for family business is a cassava chips industry that able to produce 30 kg/day. If the selling price is IDR 40,000/kg, and the production cost is IDR 25,000/kg, then the profit is IDR 450,000/day (IDR 13,500,000/month). Whereas previously their average income is IDR 50,000/day. Thus, there is a significant increase in income. Development of ecotourism using green entrepreneurship concept is in line with the national development focus in 2018 such as: manufacturing sector (industry), agriculture and tourism. Based on data, in 2013 the poverty rate in Keranggan is still very high. So, the aims of this research are: to find the way to increase income for family business through green entrepreneurship, how to encourage the community and implement green entrepreneurship as well